2022
DOI: 10.1186/s40814-022-01110-3
|View full text |Cite
|
Sign up to set email alerts
|

The AktiWeb study: feasibility of a web-based exercise program delivered by a patient organisation to patients with hip and/or knee osteoarthritis

Abstract: Background Patient organisations may be an under-utilised resource in follow-up of patients requiring long-term exercise as part of their disease management. The purpose of this study was to explore the feasibility of a web-based exercise program delivered by a patient organisation to patients with hip and/or knee osteoarthritis (OA). Methods In this pre–post feasibility study, patients aged 40–80 years with hip and/or knee OA were recruited from D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The data are collected in a study assessing feasibility of a web-based aerobic exercise programme for patients with OA ( 8 ). The exercise programme and methods of delivery are described in detail elsewhere ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data are collected in a study assessing feasibility of a web-based aerobic exercise programme for patients with OA ( 8 ). The exercise programme and methods of delivery are described in detail elsewhere ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…The data are collected in a study assessing feasibility of a web-based aerobic exercise programme for patients with OA ( 8 ). The exercise programme and methods of delivery are described in detail elsewhere ( 8 ). Patients aged 40–80 years, referred to Diakonhjemmet Hospital, Oslo, Norway for surgical consultation due to hip or knee OA, were eligible if not considered candidates for surgery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the pandemic, research indicated that the level of digitalization among POs varied widely. While many relied primarily on basic digital communication tools such as websites, email, and social media, others embraced advanced technologies and developed interactive platforms, mobile applications, or electronic patient databases to enhance the use of digital patient data for research [14][15][16]. These differences in digitalization levels may be linked to the organizational characteristics described above, as well as additional factors such as the digital literacy of PO leadership and members and their demographic profile [14].…”
Section: Introductionmentioning
confidence: 99%